Heart rate response to professional road cycling: the Tour de France - Lucia, A.; Hoyos, J.; Carvajal, A.; Chicharro, J. L. (International Journal of Sports Medicine, 1999)
The aim of the present investigation was to evaluate the heart rate response of 8 professional cyclists (26+/-3 yr; 68.9+/-5.2 kg; V02max: 74.0+/-5.8 ml x kg(-1) x min(-1)) during the 3-week Tour de France as an indicator of exercise intensity. Subjects wore a heart rate telemeter during 22 competition stages and recorded data were analysed using computer software. Two reference heart rates (corresponding to the first and second ventilatory thresholds or VT1 and VT2) were used to establish three levels of exercise intensity defined as phases I (<VT1), II (VT1 -VT2) and III (<VT2). The average total time spent by each subject in each of the 3 phases respectively was approximately 71, 23 and 8 h. The relative contributions of each phase were 70, 23 and 7%. The percentage relative contribution of each phase was significantly different (p<0.01) in each of the competition stages (time trials, flat stages, "high-mountain" stages and "medium-mountain" stages). Exercise intensity was particularly high during the time trials and high mountain stages. It may be concluded that during an endurance event such as the Tour de France, although the overall contribution of moderate (VT1 to VT2) or high intensity exercise (>VT2) is substantially lower than that of light, aerobic exercise (<VT1), a clear distinction must be made between the different type of stages (i.e. easy, flat parcours vs mountain stages or time trials) and the role of each cyclist in the team must be also considered.